Analysis of the concept of "teaching" college professors: A qualitative study - Hawes Barrios, Gustavo; Donoso Diaz, Sebastián (Education Policy Analysis Archives, 2003)
This article explores the conceptions of learning and teaching among university teachers with no pedagogical qualifications. The model of implicit theories is used as a frame of reference, and the analytical process is supported by psychological theories of learning. Observations were carried out in a public university in southern Chile. Results evidence a rather mechanistic vision of learning, associated with a vision of teaching resting on the concept of transmission, although there are some efforts to link this conception with data processing. The vision of the professional teacher is more romantic than professional.